2017
DOI: 10.1177/1179554917738765
|View full text |Cite
|
Sign up to set email alerts
|

Salvage Low Dose Rate Brachytherapy For Recurrent Prostate Cancer After External Beam Radiotherapy: Results From A Single Institution With Focus On Toxicity And Functional Outcomes

Abstract: Background/aim:Low dose rate brachytherapy has been used as salvage therapy for locally recurrent prostate cancer (PC) after primary external beam radiation therapy (EBRT), along with surgery and cryotherapy. All these techniques, in particular, when applied to the whole gland, involve a relatively high risk of toxicity and may worsen the patient’s quality of life. Our aim is to evaluate the results of whole-gland salvage brachytherapy (SBT) after primary EBRT in terms of toxicity, functional outcomes, and eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The use of interventional radiotherapy (BT) has increased in the last decades, most probably due to technical improvements, allowing to deliver higher doses to the target while reducing dose and volume of organs at risk [ 9 ]. Moreover, BT in Italy has been increasingly based on a multidisciplinary approach, with a growing number of high-quality publications of excellent treatment results [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. These innovations, in the context of a rapid diffusion of 3D planning, with an increased use of computed tomography (CT), magnetic resonance imaging (MRI), positron emission tomography (PET)/CT, and ultrasound, favored the diffusion of image-guided brachytherapy (IGBT) [ 32 ] with related clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…The use of interventional radiotherapy (BT) has increased in the last decades, most probably due to technical improvements, allowing to deliver higher doses to the target while reducing dose and volume of organs at risk [ 9 ]. Moreover, BT in Italy has been increasingly based on a multidisciplinary approach, with a growing number of high-quality publications of excellent treatment results [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 ]. These innovations, in the context of a rapid diffusion of 3D planning, with an increased use of computed tomography (CT), magnetic resonance imaging (MRI), positron emission tomography (PET)/CT, and ultrasound, favored the diffusion of image-guided brachytherapy (IGBT) [ 32 ] with related clinical benefits.…”
Section: Discussionmentioning
confidence: 99%
“…When we take into account radical salvage modalities, surgery seems to be the treatment of choice and for a considerable length of time was the only option. [1][2][3][4][5][6] Later on, some new possibilities such as cryotherapy, 7,8 high-intensity focused ultrasound (HIFU), 9,10 and brachytherapy (BT) [11][12][13][14][15][16][17][18] appeared. All the aforementioned modalities have yielded promising results but not consistently-primarily due to limited availability, patient performance status and/or comorbidities, local anatomical conditions, and a lack of patient agreement.…”
Section: Introductionmentioning
confidence: 99%
“…Two studies reported IPSS and IIEF scores after whole-gland salvage treatments, namely whole-gland salvage LDR-BT (n = 19) and whole-gland salvage HIFU (n = 81). The questionnaires revealed a peak to moderate urinary symptoms (mean IPSS ±15) and a deterioration to severe ED (mean IIEF ±6) in the first year [15] , [16] . Another study on whole-gland salvage HIFU in 61 patients used the University of California Los Angeles Prostate Cancer Index (UCLA-PCI) as patient-reported outcome measurement.…”
Section: Discussionmentioning
confidence: 99%